Risk Analysis Through Decarbonization Of Energy Systems Towards Net Zero Emissions (NZE) In Donggi Matindok Gas Field - Ridwan Kiay Demak (Eduvest - Journal of Universal Studies, 2024)
Global warming that has an impact on climate change is mostly influenced by an increase in carbon dioxide (CO2) gas in the air. Decarbonization programs in building green industrial ecosystems play an important role in achieving Net Zero Emissions (NZE) by 2060. The Objective of the study is to investigate risk control in the Decarbonization program consisting of Carbon Reduction and Carbon Capture Utilization and Storage (CCUS). The focus of the study area in this research is the Donggi Matindok gas field in Central Sulawesi. The research method is to conduct a risk analysis of the decarbonization program implemented so that it can mitigate the risk of operation failure and safety. The results of the evaluation obtained that the carbon reduction program that has been carried out consists of gas processing innovations, energy efficiency, flaring reduction has a low risk with a reduction of 22% per year from the total CO2 produced. The application of the energy management system or ISO 50001 supports in maintaining energy performance so that energy efficiency can be achieved so that the carbon reduction program can be developed every period. Then for the implementation of the CCUS program has a medium to high risk with significant CO2 reduction potential. CCUS programs that will be carried out are CCU Microalgae and CCS well Injection programs. Well targeted risk mitigation can help ensure that government efforts to support decarbonization programs are effective and successful in the long term.